Response of bacterial colonization in Nematostella vectensis to development, environment and biogeography. (30th July 2015) - Mortzfeld, Benedikt M.; Urbanski, Szymon; Reitzel, Adam M.; Künzel, Sven; Technau, Ulrich; Fraune, Sebastian
Summary: The establishment of host–bacterial colonization during development is a fundamental process influencing the fitness of many organisms, but the factors controlling community membership and influencing the establishment of the microbial ecosystem during development are poorly understood. The starlet sea anemone N ematostella vectensis serves as a cnidarian model organism due to the availability of laboratory cultures and its high tolerance for broad ranges of salinity and temperature. Here, we show that the anemone's epithelia are colonized by diverse bacterial communities and that the composition of its microbiota is tightly coupled to host development. Environmental variations led to robust adjustments in the microbial composition while still maintaining the ontogenetic core signature. In addition, analysis of bacterial communities of Nematostella polyps from five different populations revealed a strong correlation between host biogeography and bacterial diversity despite years of laboratory culturing. These observed variations in fine‐scale community composition following environmental change and for individuals from different geographic origins could represent the microbiome's contribution to host acclimation and potentially adaptation, respectively, and thereby contribute to the maintenance of homeostasis due to environmental changes.